pH-Triggered Size-Transformable and Bioactivity-Switchable Self-Assembling Chimeric Peptide Nanoassemblies for Combating Drug-Resistant Bacteria and Biofilms - Tan, Peng (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.